Ion structure in dense plasmas: MSA versus HNC - Wuensch, K; Vorberger, J; Gregori, G; Gericke, DO (2009)
We present results for the ionic structure in dense, moderately to strongly coupled plasmas using two models: the mean spherical approximation (MSA) and the hypernetted chain (HNC) approach. While the first method allows for an analytical solution, the latter has to be solved iteratively. Independent of the coupling strength, the results show only small differences when the ions are considered to form an unscreened one-component plasma (OCP) system. If the electrons are treated as a polarizable background, the different ways to incorporate the screening yield, however, large discrepancies between the models, particularly for more strongly coupled plasmas. © 2009 IOP Publishing Ltd.